Decreased number of striatal cholinergic interneurons and motor deficits in dopamine receptor 2-expressing-cell-specific Dyt1 conditional knockout mice - Fumiaki Yokoi; Janneth Oleas; Hong Xing; Yuning Liu; Kelly M. Dexter; Carly Misztal; Melinda Gerard; Iakov Efimenko; Patrick Lynch; Matthew Villanueva; Raul Alsina; Shiv Krishnaswamy; et al. (Neurobiology of Disease, 2020)
DYT1 early-onset generalized torsion dystonia is a hereditary movement disorder characterized by abnormal postures and repeated movements. It is caused mainly by a heterozygous trinucleotide deletion in DYT1/TOR1A, coding for torsinA. The mutation may lead to a partial loss of torsinA function. Functional alterations of the basal ganglia circuits have been implicated in this disease. Striatal dopamine receptor 2 (D2R) levels are significantly decreased in DYT1 dystonia patients and in the animal models of DYT1 dystonia. D2R-expressing cells, such as the medium spiny neurons in the indirect pathway, striatal cholinergic interneurons, and dopaminergic neurons in the basal ganglia circuits, contribute to motor performance. However, the function of torsinA in these neurons and its contribution to the motor symptoms is not clear. Here, D2R-expressing-cell-specific Dyt1 conditional knockout (d2KO) mice were generated and in vivo effects of torsinA loss in the corresponding cells were examined. The Dyt1 d2KO mice showed significant reductions of striatal torsinA, acetylcholine metabolic enzymes, Tropomyosin receptor kinase A (TrkA), and cholinergic interneurons. The Dyt1 d2KO mice also showed significant reductions of striatal D2R dimers and tyrosine hydroxylase without significant alteration in striatal monoamine contents or the number of dopaminergic neurons in the substantia nigra. The Dyt1 d2KO male mice showed motor deficits in the accelerated rotarod and beam-walking tests without overt dystonic symptoms. Moreover, the Dyt1 d2KO male mice showed significant correlations between striatal monoamines and locomotion. The results suggest that torsinA in the D2R-expressing cells play a critical role in the development or survival of the striatal cholinergic interneurons, expression of striatal D2R mature form, and motor performance. Medical interventions to compensate for the loss of torsinA function in these neurons may affect the onset and symptoms of this disease.